The Effect of Religious Involvement on Life Satisfaction among Korean Christians: Focused on the Mediating Effect of Spiritual Well-Being and Self-Esteem - Yoo, Jieun (Journal of pastoral care & counseling, 2017)
The present study examined the relationship between two categories of religious involvement, namely religious belief and religious behavior, and life satisfaction among Korean Christians (N = 278) with spiritual well-being and self-esteem as potential mediators in this relationship by using structural equation modeling (SEM). The results supported the full mediated structural model and indicated that religious belief had a significant indirect effect on life satisfaction through the mediators, spiritual well-being and self-esteem. Religious behavior did not have an indirect or direct effect on life satisfaction among Korean Christians. The significance, implications, and limitations of the study were discussed.